Historical Learning Media Based on Mobile Learning - Meihan, Andre Mustofa (HISTORIKA, 2020)
AbstractThe selection of instructional media that can be something urgent in the current era of information and communication technology development. The purpose of this study is to determine whether the learning media based on mobile learning can be applied to historical subjects. The method used in this research is literature study. Based on the results of the discussion, it can be concluded that the use of historical learning media based on mobile learning is needed to support the learning process and achieve learning objectives. while answering the question that, mobile learning based learning media can be applied to history subjects.